PENGARUH KONDISI KEUANGAN, REPUTASI AUDITOR, DISCLOSURE, DAN OPINI AUDIT TAHUN SEBELUMNYA PADA PENGUNGKAPAN OPINI AUDIT GOING CONCERN - Rahayuningsih, Anita (JURNAL AKUNTANSI DAN AUDITING, 2014)
Giving going concern status is not easy task because it is closely related to the auditor’s reputation.Public accountants are often judged both by society and the government to see whether or notthe insolvent condition of the company being audited. By Mirna 2007, indicates that the auditor’sreputation at stake when providing an audit opinion. Going concern opinion should be expressedin the hope to speed up efforts to rescue the troubled company. This research was conducted onthe real estate and property companies listed in Bursa Efek Indonesia (BEI) which has completefinancial statements for the year 2009-2013. The method of sample selection in this researchusing purposive sampling method. The total of observational research (5 years) of 180 samples.Methods of analysis were performed logistic regression were processed with SPSS. The resultsshowed that financial conditions had no significant effect on the disclosure of Going ConcernAudit Opinion Wald value of 0.022 (wald)<1.97 (t-table) and the significance of 0883>0.05.While the auditor’s reputation, Disclosure, and the previous year’s audit opinion a significanteffect on the disclosure of Going Concern Audit Opinion. auditor reputation value Wald 7823(wald)>1.97 (t-table) and the significance 0.005<0.05, Wald value Disclosure 4713 (wald)>1.97(t-table) and the significance 0.030<0.05, the previous year’s audit opinion the value of Wald8264 (wald)>1.97 (t-table) and the significance 0.004 <0.05